1998
DOI: 10.1073/pnas.95.22.13248
|View full text |Cite
|
Sign up to set email alerts
|

EphA4 (Sek1) receptor tyrosine kinase is required for the development of the corticospinal tract

Abstract: Members of the Eph family of tyrosine kinase receptors have been implicated in the regulation of developmental processes and, in particular, axon guidance in the developing nervous system. The function of the EphA4 (Sek1) receptor was explored through creation of a null mutant mouse. Mice with a null mutation in the EphA4 gene are viable and fertile but have a gross motor dysfunction, which is evidenced by a loss of coordination of limb movement and a resultant hopping, kangaroo-like gait. Consistent with the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
239
0
3

Year Published

2001
2001
2008
2008

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 273 publications
(254 citation statements)
references
References 37 publications
12
239
0
3
Order By: Relevance
“…The role activity-independent processes in development of the CS projection to the spinal cord is only beginning to be understood (Dottori et al 1998;Joosten and Bar, 1999;Coonan et al 2001;Liu et al 2005). After CS axon terminals contact their spinal (and brain stem) targets, activity-dependent processes are key to refining connections and establishing the mature pattern of topographic and connectional specificity.…”
Section: Overall Conclusion Role Of Activity-dependent Processes In mentioning
confidence: 99%
See 1 more Smart Citation
“…The role activity-independent processes in development of the CS projection to the spinal cord is only beginning to be understood (Dottori et al 1998;Joosten and Bar, 1999;Coonan et al 2001;Liu et al 2005). After CS axon terminals contact their spinal (and brain stem) targets, activity-dependent processes are key to refining connections and establishing the mature pattern of topographic and connectional specificity.…”
Section: Overall Conclusion Role Of Activity-dependent Processes In mentioning
confidence: 99%
“…Work in rodents has examined differentiation of CS neurons Molyneaux et al 2005) and guidance of their axons to the spinal cord (Terashima, 1995;Dottori et al 1998;Joosten and Bar, 1999;Coonan et al 2001;Liu et al 2005). Evidence shows that these processes are driven by transcriptional codes and intrinsic factors in the developing nervous system.…”
Section: Normal Development Of Cs Terminations In the Spinal Cordmentioning
confidence: 99%
“…During corticospinal tract development, Ephrin-B3 is concentrated at the spinal cord midline and prevents EphA4-expressing axon collaterals of the corticospinal tract from re-crossing the midline since they have already crossed once at the spinomedullary junction (Davy and Soriano, 2005). CST axons in either Ephrin-B3 or EphA4 mutant mice exhibit bilateral innervation of spinal grey matter due to the loss of the midline barrier (Ephrin-B3) or the receptor to sense the barrier (EphA4) (Dottori et al, 1998;Kullander et al, 2001;Yokoyama et al, 2001). Benson et al reported the expression of Ephrin-B3 in postnatal myelinating oligodendrocytes in the mouse spinal cord and provided evidence that this myelin component confers sensitivity to postnatal cortical neurons that express EphA4 (Benson et al, 2005).…”
Section: Axon Guidance Molecules: Potential New Roles For Old Moleculesmentioning
confidence: 99%
“…Mice with a null mutation of the Eph A4 gene also presented deficiencies in the anterior commissure but their most noticeable trait was an abnormal locomotion pattern, described as a kangaroolike gait that resulted from an aberrant cortico-spinal tract (Dottori et al 1998). This tract commands voluntary movement by ultimately connecting the motor cerebral cortex with interneurons and spinal cord motoneurons in the contralateral side (Kuypers 1981).…”
Section: Eph Receptors and Ephrinsmentioning
confidence: 99%
“…Although relatively normal by many standards, such animals hop rather than walk, i.e., display a kangaroo-like motor pattern (Dottori et al 1998, Kullander et al 2001.…”
Section: Introductionmentioning
confidence: 99%